Do regional trade agreements increase technology complexity of digital service export trade? Evidence from digital intellectual property rules - Zehui Yu; Lihua Dai; Jingwen Lu; Jia Li (PLoS ONE, 2025)
Based on the technology complexity data of bilateral digital service exports of 64 representative economies in the world from 2010 to 2021, this paper uses the gravity model to explore the heterogeneous trade effects of Regional Trade Agreements (RTAs) from the perspective of digital intellectual property rules. The results show that the higher the commitment level of digital intellectual property rules in RTAs signed between the contracting parties, the more conducive to the enhancement of the technology complexity of bilateral digital service trade exports, and the trade effect of RTAs is significant. The influence of the depth of digital intellectual property rules on the export technology complexity of digital service trade has heterogeneity in rule categories, economic development level of exporting countries, imitation ability of importing countries, and law enforcement gap between importing and exporting countries. The results of the mechanism test show that the digital intellectual property rules in RTAs can increase the technology complexity of digital service enterprises through the scale expansion effect of two-way FDI and the technological innovation effect of exporting countries. This paper provides policy implications for global digital intellectual property governance and the quality development of digital service trade.